Szkic o edukacji współpracy - Przybył-Ołowski, Bartosz (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
The new model of philosophical education that functions in Polish schools requires a change. In order to adapt teaching of philosophy to the needs and expectations of students it is necessary to introduce new educational method. Learning should refer to practical problems and solutions using the project method. The use of this method in education of cooperation brings extraordinary effects. Thanks to that students activate themselves socially, they become more aware of the philosophical problems, and independently develop their curiosity about the world.